Igneous sill and finger emplacement mechanism in shale-dominated formations: a field study at Cuesta del Chihuido, Neuquén Basin, Argentina - Spacapan, Juan Bautista (2016)
Seismic reflection data and field observations have revealed the presence of voluminous igneous sill complexes emplaced into organic-rich shale formations in sedimentary basins worldwide. Damage and structures associated with sills have major implications for fluid flow through basins. Constraining the distribution of these structures requires a good understanding of the sill emplacement mechanism. However, most mechanical models of sill emplacement assume elastic host behaviour, whereas shale is expected to deform inelastically. This contradiction calls for new field observations to better constrain sill emplacement mechanisms. In this paper, we report on detailed field observations of spectacularly exposed fingers and a sill emplaced in shale at Cuesta del Chihuido, in the Neuquén Basin, Argentina. Exceptional outcrop conditions allow detailed descriptions of both (1) the entire cross-section of the intrusions, and (2) the deformation structures accommodating intrusion propagation in the host rock. All intrusions exhibit irregular, blunt or rectangular tips. The structures accommodating the tip propagation are systematically compressional, including reverse faults, folding and imbricate thrust system. Our observations suggest that the studied intrusions have propagated by pushing the host rock ahead, as a viscous indenter. Our observations suggest that the viscous indenter model is probably a dominant mechanism of sill emplacement in shale.